A wearable multi-channel fNIRS system for brain imaging in freely moving subjects - Piper, Sophie K.; Krueger, Arne; Koch, Stefan P.; Mehnert, Jan; Habermehl, Christina; Steinbrink, Jens; Obrig, Hellmuth; Schmitz, Christoph H. (NeuroImage (Orlando, Fla.), 2014)
Functional near infrared spectroscopy (fNIRS) is a versatile neuroimaging tool with an increasing acceptance in the neuroimaging community. While often lauded for its portability, most of the fNIRS setups employed in neuroscientific research still impose usage in a laboratory environment. We present a wearable, multi-channel fNIRS imaging system for functional brain imaging in unrestrained settings. The system operates without optical fiber bundles, using eight dual wavelength light emitting diodes and eight electro-optical sensors, which can be placed freely on the subject's head for direct illumination and detection. Its performance is tested on N=8 subjects in a motor execution paradigm performed under three different exercising conditions: (i) during outdoor bicycle riding, (ii) while pedaling on a stationary training bicycle, and (iii) sitting still on the training bicycle. Following left hand gripping, we observe a significant decrease in the deoxyhemoglobin concentration over the contralateral motor cortex in all three conditions. A significant task-related ΔHbO2 increase was seen for the non-pedaling condition. Although the gross movements involved in pedaling and steering a bike induced more motion artifacts than carrying out the same task while sitting still, we found no significant differences in the shape or amplitude of the HbR time courses for outdoor or indoor cycling and sitting still. We demonstrate the general feasibility of using wearable multi-channel NIRS during strenuous exercise in natural, unrestrained settings and discuss the origins and effects of data artifacts. We provide quantitative guidelines for taking condition-dependent signal quality into account to allow the comparison of data across various levels of physical exercise. To the best of our knowledge, this is the first demonstration of functional NIRS brain imaging during an outdoor activity in a real life situation in humans. •A wearable, multi-channel fNIRS imaging system is presented and tested in 8 subjects.•This is the first demonstration of fNIRS brain imaging during an outdoor activity.•The device is well feasible for functional brain imaging in real life situations.